2022
DOI: 10.3390/pharmaceutics14122802
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Evaluation of Modified Chitosan Nanoparticles Using Anionic Sodium Alginate Polymer for Treatment of Ocular Disease

Abstract: Mucoadhesive nanoparticles offer prolonged drug residence time at the corneal epithelium by adhering to the mucous layer of the eye. Here, in this research investigation, voriconazole-loaded chitosan mucoadhesive nanoparticles (VCZ-MA-NPs) were modified to mucous-penetrating nanoparticles (VCZ-MP-NPs) by coating them with anionic polymer sodium alginate. The ionic gelation method was utilized to prepare mucoadhesive chitosan nanoparticles, which were further coated with sodium alginate to obtain the surface pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…As shown in the figure, the administration of 0.1 M NaOH was used as a positive control because it could induce rapid and severe bleeding, which was considered a severe irritation, while the addition of NaCl 0.9% w/v was used as a negative control because it did not cause irritation, which indicated that it was considered safe. Meanwhile, for the treatment of all DMN-SD-AMB formulas after 5 min of observation, the appearance was similar to that of the negative control, which indicated that they did not show signs of damage to blood vessels . Thus, DMN-SD-AMB did not irritate the system and was deemed safe for application in in vivo studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in the figure, the administration of 0.1 M NaOH was used as a positive control because it could induce rapid and severe bleeding, which was considered a severe irritation, while the addition of NaCl 0.9% w/v was used as a negative control because it did not cause irritation, which indicated that it was considered safe. Meanwhile, for the treatment of all DMN-SD-AMB formulas after 5 min of observation, the appearance was similar to that of the negative control, which indicated that they did not show signs of damage to blood vessels . Thus, DMN-SD-AMB did not irritate the system and was deemed safe for application in in vivo studies.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, for the treatment of all DMN-SD-AMB formulas after 5 min of observation, the appearance was similar to that of the negative control, which indicated that they did not show signs of damage to blood vessels. 39 Thus, DMN-SD-AMB did not irritate the system and was deemed safe for application in in vivo studies.…”
Section: Water Vapor Transmission Rate (Wvtr) Studymentioning
confidence: 94%
See 2 more Smart Citations
“…For the study, the cornea was separated from the eyeball and was cleaned thoroughly to remove any other adhered tissue using a standard solution. (Bhosale et al, 2022) The goat cornea was uniformly spread between the acceptor and donor compartment, as shown in Figure 1(B(iii)). After that, 14ml of PBS buffer at pH 7.4 was placed into the receptor compartment such that the cornea was in close contact with the buffer media.…”
mentioning
confidence: 99%